Formulation and packaging of "Mongo-Coconut Flour Biscuits." - Carreon, Flor de Lis B.; Guzman, Matilde P. (1968, 1968)
A protein-rich blend of mongo flour, coconut flour, and Brewer's yeast with a ration of 70:25:5 was incorporated into a biscuit with 10.69% protein. The biscuits were packed in three different types of packaging films, namely, ploy-foil-cello laminate, polyethylene, and cello-polyethylene pillow-type bags, and the effectiveness of these films in maintaining the quality of the product was evaluated by periodic determinations of weight changes, free fatty acids expressed as % oleic acid, peroxide value, and subjective evaluation. Results showed poly-foil-cello laminate film to be the best packaging material, followed by polyethylene, and lastly by cello-polyethylene. The poly-foil-cello laminate-wrapped samples were found to approximate the control in overall quality.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Biscuits; Coconut flour